The photographs of IBGE field trips in the Revista Brasileira de Geografia (1939-1968): a quantitative analysis - Lara D'Assunção dos Santos (Geografares, 2022)
This research is dedicated to the study of photographs of expeditions, excursions and fieldwork of the Brazilian Institute of Geography and Statistics (IBGE) that circulated in the Brazilian Journal of Geography (RBG) between 1941 and 1968. The objective of the fieldwork was to identify aspects of the Brazilian reality that were hitherto unknown, an activity carried out through the research methods used by international geographic institutions and societies. The results were published in the RBG, the representative of the new IBGE geographic methodologies, which was anchored in different types of images, such as photographs, maps and sketches that revealed the processes of occupying the Brazilian territory. The objective of this work is to carry out a quantitative analysis of all the photographs and images in order to identify the moments in which the IBGE used the photographs more vehemently, intertwining them with the history of Brazil, the institute and geography.